Effectiveness of transverse tibial bone transport in treatment of diabetic foot ulcer: A systematic review and meta-analysis - Hu, Xing-xi; Xiu, Zheng-zhong; Li, Gui-chun; Zhang, Ji-yuan; Shu, Long-jun; Chen, Zhong; Li, Han; Zou, Qing-feng; Zhou, Quan (Frontiers in Endocrinology, 2023)
Background: Diabetic foot ulcerations (DFUs) are a common but highly morbid complication of long-standing diabetes, carrying high rates of associated major amputation and mortality. Transverse tibial bone transport (TTT) has recently been applied for treatment of DFUs with the aim of accelerating wound healing. This study was performed to evaluate the effectiveness and safety of TTT in patients with DFUs. Methods: Two authors independently retrieved the platforms of PubMed, Embase and CENTRAL, to identify studies associated with treatment of DFUs with TTT. Quantitative meta-analyses were performed to pool all available outcomes about the effectiveness and complications of TTT operation, with fixed- (I2<50%) or random-effect (I2>50%) model according to I2. Results: A total of 7 studies, involving 818 participants, were included, with 661 participants treated with TTT operation. The pooled healing rate and limb salvage rate were 0.96 (95%CI: 0.93 0.98) and 0.98 (95%CI: 0.95 1.00) respectively after treatment with TTT. The pooled mean healing time was 15.03 (95%CI: 9.05 21.00) months. When compared with the pre-operative baseline values, the ABI (MD: 0.23; 95%CI: 0.03 0.44; p<0.001), skin temperature (MD: 1.56; 95%CI: 0.30 2.81; p<0.001), and VAS (MD: 3.70; 95%CI: 1.97 5.44; p<0.001) were significantly improved at the final follow-up. When compared with non-TTT group, the TTT group was associated with higher healing rate (OR: 10.43; 95%CI: 3.96 27.43; p<0.001) and limb salvage rate (OR: 9.65; 95%CI: 3.30 28.20; p<0.001). Concerning the complications of the TTT process, the pooled risks of fracture at transportation site and pin-site infection were 0.02 (95%CI: 0.00 0.04) and 0.08 (95%CI: 0.00 0.22), respectively; and the DFU recurrence rate in TTT group was significantly lowered comparing to that of the non-TTT group (RR: 0.18; 95%CI: 0.06 0.49; p=0.001). Conclusions: TTT operation was associated with high healing rate and limb salvage rate, and could significantly improve the ABI, skin temperature, and VAS after operation. When compared with the control group, TTT group provided significantly higher healing rate and limb salvage rate. However, TTT operation should be conducted with caution concerning the incidences of fracture at tibia, infection at pin channels and necrosis of skin overlying the anterior tibia.